IMPLEMENTATION OF THE PRINCIPLE OF â€œKNOWING THE CUSTOMERâ€ IN GRANTING HOME OWNERSHIP LOANS AT BANK BTN CABANG SURABAYA - M.T.V.M., Sri Maharani; Laksono, Pambudi Tri (Jurnal Al-Dustur, 2023)
This research discusses the implementation of Know Your Customer Principles in granting home ownership loans at BTN Bank Surabaya Branch. This research uses a type of empirical juridical method that is data analysis and starting from primary data. Sources of data obtained through interviews with the Loan Officer / Consumer Lending Unit Staff at Bank BTN Cabang Surabaya, legislation, dictionaries, books that are still valid. Data collection methods using interviews and literature studies. The data analysis method uses a qualitative approach. The results and discussion of the research can be concluded that the implementation of the principle of knowing the customer in granting home ownership loans at Bank BTN Cabang Surabaya is basically in accordance with the basic provisions of Bank Indonesia Regulation 5/21 / PBI / 2003 on Amendments to Bank Indonesia Regulation 3 / PBI / 2001 concerning Implementation of the Know Your Customer Principle, but on the other hand there are still frequent defaults in granting home ownership loans caused by customers who was not trustworthy, based on data in 2018, 2019, 2020, 2021 and 2022 as many as 519 customers have defaulted. Thus, if defaults continue to occur in the health of the bank decreases and suffers losses, therefore things can be done with 2 (two) legal protections, namely preventive law and reprensive law. This settlement is carried out by non-litigation and litigation channels that seek to resolve problem loans so that the bank continues to run its business without being constrained and the bank can open its newest products.